Knowledge of Mothers Regarding Home Care of Children undergone Cardiac Surgery with a View to Develop an Information Booklet - Poudel, Pramila; Malla, Chandni (Med Phoenix, 2017)
Background: Children in developing countries are now receiving surgical repair for congenital heart defects. Despite advancement in the medical and surgical field, in developing countries where we have severe budgetary constraints, lack of funding for maintenance, poverty, skilled manpower deficit and knowledge deficit among public, pediatric cardiac surgery still remains a major challenge. For the parents of those children undergone corrective surgery more in-depth educational sessions are required to enable them to recognize and anticipate the complications so as to manage their child effectively at home following discharge. The study aims to assess the knowledge regarding home care of children undergone cardiac surgery with a view to develop an information booklet in home care. Methods: A descriptive cross-sectional study was conducted among 60 mothers of children undergone cardiac surgery at a tertiary level cardiac center at Bengaluru, India using a structured knowledge questionnaire. Results: Result revealed that majority 55% of the mothers had moderate knowledge, 40% had inadequate knowledge and only 5% had adequate knowledge. Variables such as age, education, occupation of mothers and source of information were significantly associated (p <0.05) with the level of knowledge. Conclusions: The knowledge of mothers regarding home care of children undergone cardiac surgery was found to be insufficient to enable them to take care of their children. The inadequate knowledge can be effectively strengthened through information booklet, discharge teaching and other mass media used as a source of information in educating not only the mothers of children but also other family members who acts as a care taker. Med Phoenix Vol.2(1) July 2017, 38-43